Розробка системи електронної комерції з продажу зоотоварів - Горюнова, М. С. (ХНУРЕ, 2024)
The article discusses the created e-commerce information system for an online pet shop. It is designed to store, easily search, place an order, and view information about the products of this store. The relevance of creating this information system is to facilitate the ordering of large volumes of goods for pets and a variety of choices of feed and accessories. This information system allows the client to get acquainted with the list of all products in stock, learn more about the product of interest or find out the price. The use of this technology will significantly increase the customer base, turnover and profit of the pet store. To implement the web application, it is proposed to use the Java programming language with the Spring Framework and the MySQL database platform.
Keywords: електронна комерція; продаж зоотоварів; система продажу; інтернет-магазин